Use of the visual analog scale of craving in addiction medicine: advantages and limitations of the method - Evgeny M. Krupitsky; Elvina A. Akhmetova; Svetlana G. Klimanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
Craving for psychoactive substances is a hallmark feature of psychoactive substance use and one of the central symptoms of substance use disorder in the DSM-5 and ICD-10. However, the debates about its precise definition, operationalization, and appropriate methods of assessment continue to this day, thus underscoring the complexity and multifaceted nature of this phenomenon. Understanding the mechanisms and dynamics of craving holds significant theoretical and practical implications for both research and clinical practice. The article explores the challenges inherent in conceptualizing craving and discusses the main strengths and limitations of current assessment methods, including self-report and experimental approaches, with a particular focus on visual analog scales (VAS). The VAS are widely regarded as rapid, simple and flexible tool that is adaptable to diverse research paradigms, requires minimal financial and time investments, places minimal low demands on respondents. Recent studies further demonstrated that the VAS has acceptable psychometric properties for assessing craving. Nevertheless, the use of VAS has its limitations. In addition to the inherent constraints of self-report methods, such as reliance on self-reflection, the VAS requires a clear definition of the construct being measured, lacks norms or thresholds, and maybe affected by the variability of how the respondents interpret maximum and intermediate scale values. When employing the VAS to assess craving, it is essential to account for the dynamic and multifaceted nature of the phenomenon. This requires careful selection of the terminology used in the instruction, the choice of the specific aspects of craving being measured, the temporal framework of assessment (“here and now” vs over a defined period of time), and the frequency and duration of measurement.